Abusive use of anabolic androgenic steroids, male sexual dysfunction and infertility: an updated review - Azevedo, Rafael de Almeida; Gualano, Bruno; Teixeira, Thiago Afonso; Nascimento, Bruno C. G.; Hallak, Jorge (Frontiers in Toxicology, 2024)
The evolving prevalence of anabolic androgenic steroids (AAS) abuse among nonathletes is alarming because of the known harm to an individual's health. Among the adverse effects of AAS abuse, male infertility and sexual dysfunction have been often reported in the literature, but little is known regarding its actual prevalence, possible underpinning mechanisms, and potential treatments either during or post-AAS usage. Thus, the current narrative review summarizes the state-of-art regarding the effects of AAS on male fertility and sexual function. Evidence was gathered from the latest reviews and recent original studies, specifically from prospective cohorts and clinical trials, ultimately resulting in five main topics of discussion. First, AAS usage is briefly characterized by its historical background, main physiological mechanisms, and the most frequently used AAS substances. Second, data on the prevalence of AAS-induced male infertility and sexual dysfunction are described. Third, some new insights on possible underpinning mechanisms of AAS-induced male infertility and sexual dysfunction are thoroughly discussed, with particular attention to histological data derived from animal models and the latest insights from prospective cohorts in humans. Fourth, the potential treatments during and after the AAS usage are presented, highlighting the odds of resolving male infertility and sexual dysfunction.Fifth, future directions on this topic are discussed, focusing on the methodological robustness of scientific studies.